Synthesis of 1, 3‐Disubstituted Imidazo[1, 5‐a]pyridines through Oxidative C‐N Bond Formation from Aryl‐2‐pyridylmethanols and Their Fluorescent Study. Issue 19 (21st May 2019) - Chandrasekar, Selvaraj; Sangeetha, Subramani; Sekar, Govindasamy
Abstract: A simple, effortless, and efficacious protocol for the synthesis of highly fluorescing imidazo[1, 5‐ a ]pyridines via copper catalyzed inter‐/intramolecular C−N bond formation between readily available pyridyl alcohols with either benzyl amines or amino acids has been developed. This domino reaction is involved with alcohol oxidation/condensation/oxidative amination sequence to synthesize imidazo[1, 5‐ a ]pyridines in good to excellent yields. The fluorescence studies of these compounds indicated a bathochromic shift for the electron donating substituents, whereas a hypsochromic shift for the electron withdrawing substituents. Synthetic modification of the groups attached to the heterocyclic core showed a profound impact on the emission properties when subjected to pH and solvent polarity change. Abstract : Domino synthesis of imidazo[1, 5, a ]pyridines is reported using easily accessible pyridyl alcohols with either benzyl amines or amino acids using Cu‐catalyst. This domino mechanistic process follows oxidation/condensation/oxidative amination to give the corresponding imidazo[1, 5, a ]pyridines in good yields. Further, fluorescence property has been studied for the different substituted imidazo[1, 5, a ]pyridines.